2020
DOI: 10.1002/joc.6817
|View full text |Cite
|
Sign up to set email alerts
|

Climatology and trends of reference evapotranspiration in Spain

Abstract: This study presents a climatology and trend analysis of reference crop evapotranspiration (ET o) over continental Spain and the Balearic Islands. Geographic features of the study region play a substantial role in the climatology of ET o. The highest values (in excess of 1,200 mm y −1) are found at lower elevations in the south, while the lowest values (less than 900 mm y −1) are found in the highest elevations in the north. A deep analysis reveals: (a) a low interannual variability; (b) summer accumulates more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 81 publications
1
18
0
1
Order By: Relevance
“…In addition to the markedly seasonal character indicating the role of AED in the development of flash droughts, we also found a strong spatial component determining the role of AED in these events in Spain. The AED shows strong spatial differences in Spain, with a clear north-south gradient between the humid regions of the north and the drier regions of southern and central Spain [36,39]. Several studies suggested that the contribution of AED is much higher in dry regions than in humid ones, since its role is only important during periods of low precipitation or limited soil moisture [9,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the markedly seasonal character indicating the role of AED in the development of flash droughts, we also found a strong spatial component determining the role of AED in these events in Spain. The AED shows strong spatial differences in Spain, with a clear north-south gradient between the humid regions of the north and the drier regions of southern and central Spain [36,39]. Several studies suggested that the contribution of AED is much higher in dry regions than in humid ones, since its role is only important during periods of low precipitation or limited soil moisture [9,17].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed the high occurrence of severe droughts episodes in Spain through historical [28][29][30] and instrumental records [31]. Spain has strong climatic contrasts with marked spatial and seasonal differences in precipitation [32][33][34][35] and AED [36][37][38][39]. Northern Spain is characterized by its humid oceanic climate with abundant precipitation over the year, while northeastern and southeastern regions are mainly characterized by semiarid conditions with annual precipitation generally below 300 mm [40].…”
Section: Introductionmentioning
confidence: 99%
“…According to the values obtained for the F statistics in the different seasons, the highest increments of ET 0 are observed for spring, while the lowest variation has been obtained for summer. Tomas-Burguera et al [107] analyzed the evolution of the ET 0 in Spain for the period 1961-2014, and they also obtain the highest increments of ET 0 for the study area in spring. The results obtained in both works for that season may have or may be already having repercussions in water resources availability, these repercussions should be analyzed in future studies.…”
Section: Regionalized Model Simple Ensemble Regression Based Ensemble...mentioning
confidence: 88%
“…Because the calculations with the WBS methods showed the occurrence of numerous breakpoints in the analysed indicators of flow changes within individual rivers and corresponding indicators within all rivers, multitemporal trend analysis was applied. Following McCabe and Wolock [49] and Tomas-Burguera et al [50], the Mann-Kendall and Sen test statistics were calculated for every possible combination of start and end years in 1951-2020 for DL7, YM, TBQ50, TBQ90 and TQ5090%. This involved performing 1327 calculations for each flow indicator.…”
Section: Methodsmentioning
confidence: 99%